Risk factors for Dandy–Walker malformation: A population‐based assessment. (1st May 2015) - Reeder, Matthew R.; Botto, Lorenzo D.; Keppler‐Noreuil, Kim M.; Carey, John C.; Byrne, Janice L. B.; Feldkamp, Marcia L.; the National Birth Defects Prevention Study
<x xml:space="preserve">Abstract</x> Dandy–Walker malformation (DWM) is the most common congenital malformation of the cerebellum, but its causes are largely unknown. An increasing number of genes associated with congenital cerebellar malformations have been identified; however, few studies have examined the potential role of non‐genetic, potentially modifiable risk factors. From the National Birth Defects Prevention Study, we examined maternal, paternal, and infant characteristics and maternal conditions and periconceptional exposures (from 1 month before to 3 months after conception) among infants with DWM (n = 160) and unaffected controls (n = 10, 200), delivered between 1997 and 2009. Odds ratios, crude (cOR) and adjusted (aOR) were computed using logistic regression. Maternal factors associated with DWM included non‐Hispanic black race/ethnicity (aOR = 2.0, 95%CI: 1.3–3.2). Among maternal conditions, a history of infertility increased the risk for DWM (all: aOR = 2.4, 95%CI: 1.3–4.6; multiple: aOR = 3.9, 95%CI: 1.7–8.9). The lack of association with many maternal exposures supports the hypothesis of a major contribution of genetic factors to the risk for DWM; however, the observed associations with maternal non‐Hispanic black race/ethnicity and maternal history of infertility indicate that further research into factors underlying these characteristics may uncover potentially modifiable risk factors, acting alone or as a component of gene–environment interactions. © 2015 Wiley Periodicals, Inc.